Lumped Parameter Model for Silicon Crystal Growth from Granulate Crucible. Issue 8 (16th June 2020) - Lorenz‐Meyer, M. Nicolai L.; Menzel, Robert; Dadzis, Kaspars; Nikiforova, Angelina; Riemann, Helge
Abstract: In the present paper, a lumped parameter model for the novel Silicon Granulate Crucible (SiGC) method is proposed, which is the basis for a future model‐based control system for the process. The model is analytically deduced based on the hydromechanical, geometrical, and thermal conditions of the process. Experiments are conducted to identify unknown model parameters and to validate the model. The physical consistency of the model is verified using simulation studies and a prediction error of below 2% is reached. Abstract : Herein, a lumped parameter model for the novel Silicon Granulate Crucible (SiGC) method is proposed, which is the basis for a future model‐based control system for the process. The model is analytically deduced based on the physical conditions of the process. Experiments are conducted to identify the model parameters and the physical consistency is verified using simulation studies.